Bioclimatic zoning for Dorper sheep in the state of Pernambuco, Brazil - Mendes, Aline Medeiros de Paula; de Azevedo, Marcílio; Lopes, Pabrício Marcos Oliveira; Moura, Geber Barbosa de Albuquerque (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to perform the bioclimatic zoning for Dorper sheep, in the state of Pernambuco, Brazil. Average daily meteorological data from 246 meteorological stations in the state were used. The variables air temperature and air relative humidity were used to calculate the temperature and humidity index. With the values of these variables, isolines were traced using the Surfer software. The Agreste region of Pernambuco shows the best weather conditions for Dorper breed throughout the year than the region comprising the coast, “Zona da Mata”, and “Semiárido”. In the warmer months and in critical regions, as the “Sertão”, the implementation of management is required, to provide shade to mitigate heat stress and not compromise the productive performance of the breed .